Eastern Region Transport Survey Volume IV Part I: Highways and Highway Transport - Planning Commission (Planning Commission, 1967)
This volume provides a detailed examination of the highway and highway transport sector in India's Eastern Region during the mid-1960s. It covers historical context, planning, administration, technical standards, economic aspects, and regulatory frameworks, offering a foundational understanding for future development and policy decisions in the region.
Regional Transport Survey Unit Eastern Region, Calcutta Planning Commission Government of India
Regional Transport Survey Unit Eastern Region, Calcutta
Keywords: Early Roads in India; Administrative Developments; Jayakar Committe; National Highways; Central State Co-operation; Growth of the Vehicle Fleet; Motor Vehicle’Regulation; Inter-State Transport Commission; Motor Transport Taxation; Taxation Pattern; Nagpur Plan